Implementasi Asas Keseimbangan Bagi Para Pihak dalam Perjanjian Baku - Aryo Dwi Prasnowo; Siti Malikhatun Badriyah (Jurnal Magister Hukum Udayana (Udayana Master Law Journal), 2019)
Businessman are required to increase the efficiency of transaction time in serving consumers, therefore a practical agreement is made and the contents have been determined by one party so that the other party does not have the opportunity to negotiate and is in the position of "take it or leave it". The standard agreement does not reflect the principle of the balance of the parties to the contract. The method used in this study is normative juridical, which refers to legal norms contained in the legislation, court decisions, using data in the form of qualitative data and using a descriptive analytical approach. In the event of an imbalance during the formation or arrangement of an agreement, the contents of the agreement or implementation of the agreement, the principle of balance is present by offering a general responsibility for the application of a variety of norms as well as assessing and determining whether there is a fair agreement. To create a balance of rights and obligations of the parties in this case, an agreement needs to contain the principle of balance, fairness and fairness which is a guideline as well as a sign in regulating and forming agreements that will be made so that eventually it will become an agreement that applies to the parties.